2008
DOI: 10.1038/bjp.2008.361
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptors and asthma in humans

Abstract: According to an executive summary of the GINA dissemination committee report, it is now estimated that approximately 300 million people (5% of the global population or 1 in 20 persons) have asthma. Despite the scientific progress made over the past several decades toward improving our understanding of the pathophysiology of asthma, there is still a great need for improved therapies, particularly oral therapies that enhance patient compliance and that target new mechanisms of action. Adenosine is an important s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 94 publications
(155 reference statements)
0
37
0
Order By: Relevance
“…The involvement of adenosine in asthma has been the subject of considerable attention over the years, after it was shown that it produced powerful bronchoconstriction in asthma, although it had little effect in healthy lungs; xanthines, antagonists of adenosine receptors, were widely used for treatment of asthma (for reviews, see Persson, 1982;Kawasaki et al, 1983;Holgate et al, 1987Holgate et al, , 1990Feoktistov and Biaggioni, 1996;Fozard and Hannon, 2000;Meade et al, 2001;Fozard and McCarthy, 2002;Holgate, 2002Holgate, , 2005Polosa et al, 2002;Fozard, 2003;Lee et al, 2003;Livingston et al, 2004;Caruso et al, 2006Caruso et al, , 2009Russo et al, 2006;Brown et al, 2008b;Wilson, 2008). It was suggested that the hyper-responsive effects of adenosine in isolated bronchi was due to indirect actions by liberation of histamine and leukotrienes (Björck et al, 1992).…”
Section: A Asthmamentioning
confidence: 99%
“…The involvement of adenosine in asthma has been the subject of considerable attention over the years, after it was shown that it produced powerful bronchoconstriction in asthma, although it had little effect in healthy lungs; xanthines, antagonists of adenosine receptors, were widely used for treatment of asthma (for reviews, see Persson, 1982;Kawasaki et al, 1983;Holgate et al, 1987Holgate et al, , 1990Feoktistov and Biaggioni, 1996;Fozard and Hannon, 2000;Meade et al, 2001;Fozard and McCarthy, 2002;Holgate, 2002Holgate, , 2005Polosa et al, 2002;Fozard, 2003;Lee et al, 2003;Livingston et al, 2004;Caruso et al, 2006Caruso et al, , 2009Russo et al, 2006;Brown et al, 2008b;Wilson, 2008). It was suggested that the hyper-responsive effects of adenosine in isolated bronchi was due to indirect actions by liberation of histamine and leukotrienes (Björck et al, 1992).…”
Section: A Asthmamentioning
confidence: 99%
“…Although DPCPX treatment did not reverse influenza A virusinduced pulmonary edema, the beneficial effects of this drug on arterial oxygenation suggest that A 1 -AdoR antagonists such as DPCPX may be of some value in this regard, either on their own or as adjuncts to other therapeutic agents. Importantly, additional A 1 -AdoR antagonists are in development for other indications, and they appear to be safe and well tolerated in humans (85).…”
Section: Fig 7 Lung Compliance and Airway Resistance Were Not Alteredmentioning
confidence: 99%
“…Adenosine receptors have been described on a number of different cell types that are important in the pathophysiology of asthma, including dendritic, antigen-presenting cells, human airway epithelial and bronchial smooth muscle cells, lymphocytes, mast cells, eosinophils, neutrophils, macrophages, fibroblasts and endothelial cells (Thiel et al 2003; Young et al 2006; Wilson 2008). Activation of ARs on these different cell types is responsible for inducing the release of mediators and cytokines, leading to BHR, inflammation, edema, and airway remodeling.…”
Section: Adenosine Receptors In Asthmamentioning
confidence: 99%